Moment conditions for dynamic panel logit models with fixed effects - Bo E. Honoré; Martin Weidner (Centre for Microdata Methods and Practice (cemmap), 2020)
This paper builds on Bonhomme (2012) to develop a method to systematically construct moment conditions for dynamic panel data logit models with fixed effects. After introducing the moment conditions obtained in this way, we explore their implications for identification and estimation of the model parameters that are common to all individuals, and we find that those common model parameters are estimable at root-n rate for many more dynamic panel logit models than has been appreciated by the existing literature. In the case where the model contains one lagged variable, the moment conditions in Kitazawa (2013, 2016) are transformations of a subset of ours. A GMM estimator that is based on the moment conditions is shown to perform well in Monte Carlo simulations and in an empirical illustration to labor force participation.
Keywords: 330; Logit-Modell; Panel; Dynamische Wirtschaftstheorie; Momentenmethode; Erwerbstätigkeit; Theorie; USA